Room temperature ferromagnetic behavior in pressed pellets of doped poly (3-methylthiophene) - De Oliveira, AJA; Pereira, E. C.; Walmsley, L.; Correa, A. A.; Ortiz, W. A.; Bulhoes, LOS (Taylor & Francis Ltd, 2002)
Room temperature ferromagnetic behavior has been observed in pressed pellets of doped poly(3-methylthiophene). In this work we show that thermoremance data taken in two different ways favours the interpretation of data in terms of the Dzialoshinski-Moriya anisotropic superexchange interaction of the polarons via dopant anions giving rise to weak ferromagnetism.
Keywords: conducting polymers; polarons; weak ferromagnetism; antiferromagnetism